2016
DOI: 10.3109/0284186x.2015.1115118
|View full text |Cite
|
Sign up to set email alerts
|

Trends in breast cancer in the elderly in Denmark, 1980–2012

Abstract: Background Breast cancer is the most frequent malignancy among women worldwide and the second most common cause of cancer-related death in developed countries. The aim of the present analysis is to describe trends in incidence, mortality, prevalence, and relative survival in Denmark from 1980 to 2012 focusing on age, comparing persons aged 70 years or more with those aged less than 70 years. Material and methods Cancer of the breast was defined as ICD-10 code C50. Data derived from the NORDCAN database with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In the oldest age group, this may in part be explained by the fact that not all patients are permanently cured and may die from the disease at an older age. However, the possibility of undertreatment at older ages cannot be excluded . The Danish Breast Cancer Group's treatment protocols did not cover the oldest patients until 2002, and no adjuvant chemotherapy was recommended for patients above 70 years of age before 2007 .…”
Section: Discussionmentioning
confidence: 99%
“…In the oldest age group, this may in part be explained by the fact that not all patients are permanently cured and may die from the disease at an older age. However, the possibility of undertreatment at older ages cannot be excluded . The Danish Breast Cancer Group's treatment protocols did not cover the oldest patients until 2002, and no adjuvant chemotherapy was recommended for patients above 70 years of age before 2007 .…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis after breast cancer is determined by patient characteristics, such as age and comorbidities; disease related factors, such as stage of disease; and treatment. Recent data from Denmark demonstrate that the relative survival decreases with age above 70 years [3]. The proportion of patients with comorbidities increases with age from 13% of patients aged 50-59 years to 40% among patients aged 80 years or more [4].…”
Section: Introductionmentioning
confidence: 99%
“…A major subgroup with guideline violations seems to be patients with higher age (20)(21)(22)(23). Several comparable results have demonstrated that higher age remains a barrier to receiving chemotherapy for EBC, as has been shown, for example, in France (24), Denmark (25), Spain (26), and the US (27). In Germany, the most important reason for discouraging patients from undergoing chemotherapy is somatic comorbidities and age > 75 years (19).…”
Section: Discussionmentioning
confidence: 90%